Between two continents: literature and narratives for humanizing doctors and patients - Maria Auxiliadora Craice De Benedetto (O Mundo da Saúde)
Teaching based exclusively on a biomechanical model has shown to be insufficient for educating good professionals in the area of medicine. With the development of the specialty named Family Medicine (FM) and its establishment in the academic setting, it was possible to go beyond this model for constructing a biopsychosocial model. Themes such as reflection, self-knowledge, feelings, beliefs, suffering, death, compassion and empathy, that have to do with the imponderable dimensions of human beings, began to be valued and tackled in medical education thanks to the introduction of the teaching of Humanities in the programs of study of several universities in the world. This article shows the benefits of including texts and literary methods, as well as the methodology called Medicine based on Narratives, as education instruments in practical-theoretical settings for teaching FM.